Siltuximab: a targeted therapy for idiopathic multicentric Castleman disease. (January 2016) - Fajgenbaum, David C; Kurzrock, Razelle
Human herpes virus-8 (HHV-8)-negative or idiopathic multicentric Castleman disease (iMCD) is a rare and deadly disorder that sits at the nexus of hematology/oncology, virology and immunology. Management of iMCD has been challenging due to limited understanding of etiology and pathogenesis and few treatment options. The recent approvals in North America, Europe and Brazil of siltuximab, a monoclonal antibody against IL-6, for iMCD now provide a safe and effective therapy that targets a key aspect of pathogenesis. In the first ever randomized, placebo-controlled trial in iMCD, siltuximab significantly reduced disease burden and symptoms in a large portion (34%) of patients. The optimal dose is 11 mg/kg intravenously every 3 weeks. At this time, duration of treatment is often life-long or until treatment failure. Additional research is needed to identify biomarkers that may assist with predicting treatment effectiveness in iMCD and to investigate the role of siltuximab in HHV-8-positive MCD and pediatric iMCD patients.